TO PROBLEM OF DEFORMED BODY DESTRUCTION. PART 1. THE MAIN EQUATIONS - Chanyshev A.I. (My University, 2001)
Phenomenon of deformed rock mass destruction has been considered. Mathematical models of rock mass destruction have been discussed. It has been shown that system of differential equations of hyperbolic type describes rock mass destruction in case of plane deformation. Relation between hydrostatic stress and maximal tangential stress is described by means of four orthogonal characteristics. Turn of rocks and value of angle characterizing the positions of the main axes of stress tensor have been shown. In order to determine various parameters on boundary of region, Cauchy stress vectors and displacements are preset.